Review of Two Siblings with Werner's Syndrome: A Case Report - Murat Sert; Koray Fakioglu; Tamer Tetiker (Case Reports in Medicine)
We report the clinical course of two siblings with Werner's syndrome (WS) who were diagnosed and followed at our clinics for 12 years. Initial diagnosis of the first sibling (sister) was at age 20, the second (brother) at 16. At the initial diagnosis, the sister had amenorrhea, muscle atrophy at arms and legs, diabetes mellitus (DM), short stature, bilateral cataracts, genital hypoplasia, osteoporosis, and gray hair. During 12 years follow-up period, high-pitched voice, hepatosteatosis, renal parenchymal disease, and urethral obstruction developed. Regarding the brother, DM, cataracts and genital hypoplasia were observed at the initial diagnosis. During the 12 years follow-up period, gray hair, high-pitched voice, steatohepatosis, and osteoporosis developed.